Acceleration of cyanobacterial dominance in north temperate-subarctic lakes during the Anthropocene - Taranu, Zofia E.; Gregory-Eaves, Irene; Leavitt, Peter R.; Bunting, Lynda; Buchaca, Teresa; Catalan, Jordi; Domaizon, Isabelle; Guilizzoni, Piero; Lami, Andrea; McGowan, Suzanne; Moorhouse, Heather; Morabito, Giuseppe; et al. (Wiley, 2015)
Increases in atmospheric temperature and nutrients from land are thought to be promoting the expansion of harmful cyanobacteria in lakes worldwide, yet to date there has been no quantitative synthesis of long-term trends. To test whether cyanobacteria have increased in abundance over the past ~ 200 years and evaluate the relative influence of potential causal mechanisms, we synthesised 108 highly resolved sedimentary time series and 18 decadal-scale monitoring records from north temperate-subarctic lakes. We demonstrate that: (1) cyanobacteria have increased significantly since c. 1800 ce, (2) they have increased disproportionately relative to other phytoplankton, and (3) cyanobacteria increased more rapidly post c. 1945 ce. Variation among lakes in the rates of increase was explained best by nutrient concentration (phosphorus and nitrogen), and temperature was of secondary importance. Although cyanobacterial biomass has declined in some managed lakes with reduced nutrient influx, the larger spatio-temporal scale of sedimentary records show continued increases in cyanobacteria throughout the north temperate-subarctic regions.